Estructura poblacional de Teline monspessulana (L.) K. Koch en fragmentos de bosque maulino en Chile central - GÓMEZ, PERSY; BUSTAMANTE, RAMIRO; SAN MARTÍN, JOSÉ (Gayana Botánica, 2012)
In this note we examine the population structure of Teline monspessulana, an exotic plant that is invading fragments of the Maulino Forest. We evaluate density T. monspessulana, sizes, proportion of reproductive individuals and his relation with the size of the patches in 8 forest fragments. Our results indicate a high proportion of individuals growing inside fragments. Moreover, the fragment size is not correlated with T. monspessulana density.